Reaching learners through telecommunications : management and leadership strategies for higher education - Duning, Becky S., 1939-, author; Van Kekerix, Marvin J., 1944-, author; Zaborowski, Leon M., 1942-, author (San Francisco : Jossey-Bass Publishers, 1993)
The advent of new telecommunications technologies - and a growing recognition of their potential for meeting educational needs - has raised many questions about how to integrate telecommunications with existing educational programs. But there is much confusion among educators about where to begin and how to proceed: what skills and experience are required? How should costs be projected, allocated, and offset? How is telecommunications-based education aligned with the current structure and mission of an institution? What standards of quality should be applied? In this book the authors offer nontechnical professionals a comprehensive guide to the process of integrating, implementing, and maintaining telecommunications-based education in their institutions and organizations. Reaching Learners Through Telecommunications offers practical advice to novice and experienced managers on every phase of administering a telecommunications-based education program, including analyzing the appropriateness of telecommunications-based education for the individual institution, determining typical expenditures and revenue sources for telecommunications-based educational programs - using one of the master budget formats provided in the book, creating a marketing strategy that successfully integrates telecommunications into the current educational marketplace and building a comprehensive resource information base of publications, associations, conferences, and agencies. This book will prove to be a valuable resource for managers of educational telecommunications systems; deans and directors of continuing higher education; administrators of distance education and postsecondary education programs; educators at the primary, secondary, and postsecondary levels; business professionals in private and public industry; and business and education consultants
Mapping the transition to telecommunications-based education -- Guiding assumptions of educational telecommunications -- Developing an action plan to minimize risk -- Assessing choices in systems design -- Management and staffing concerns -- Ensuring fiscal stability -- Developing a marketing strategy -- Integrating telecommunications-bases education into the organization -- Assessing and maintaining quality -- Sources of information about telecommunications -- Policy issues in the new telesphere -- Moving toward education for all
Includes bibliographical references and index.
Keywords: Telecommunication in education; Distance education; Education, Higher